Knowledge and Adoption of Drip Irrigation in Citrus Crops among Farmers of Western Haryana - Kumari, Vinod; Chander, Subhash; Sharma, Sushil (Indian Journal of Extension Education, 2021)
Water is becoming increasing scare which limits agricultural development not only in India but also in many parts of the world. Drip irrigation is an incredibly efficient watering method that slowly delivers water directly to plant root system. The present study was undertakento assess the knowledge and adoption level of drip irrigation in citrus crops among farmers of Haryana state. Majority of respondents belonged to middle age group (51.67%), general castes (96.67%), joint families (68.33%) and having land between 4-10 hectares(45.00%).It was found that majority of sampled farmers (61.67%) had high level of knowledge while31.67% had moderate level of knowledge of drip irrigation. More number of farmers had high level of adoption (40.00%) whereas 35.00% had medium and 25.00% had low level of adoption of drip irrigation.Socio-economic factors like income, landholding, mass media exposure, education and socio-economic status of farmers were found significantly associated with the level of knowledge and adoption of drip irrigation. It is concluded that more efforts are required to increase the knowledge of farmers about drip irrigation for wider adoption of micro-irrigation technologies.